EFFCT OF THE MANAGEMENT SYSTEM ON AWASSI SHEEP PRODUCTION - Adhab, Ahmad Ali; Al-Jalili, Zuhair Fakhri; Taha, Sadeq Ali (Diyala Agricultural Sciences Journal, 2015)
This study has been conducted at two locations, the first one was at the sheep and goat breeding station which belongs the states board of agricultural researchers/ Ministry of Agriculture which located in Akarkouf25 Km west of Baghdad. The 2nd one was in a farm of sheep owner (Private sector) in AbuGhraib, during the period from 15/5/2011 to 15/4/2012 to study the different production system and breeding system on some production performance of Awassi sheep and to study the milk production. Study include three flocks of Awassi sheep each one consist of 40 Awassi ewes.(The first one was the improved flock and the second was the unimproved flock (both of them belongs to the sheep and goats station) while the third one belong to the sheep owner). Also the born lambs of the unimproved flock were significantly (p<0.0.1) heavier than the born lambs in the improved and grazing flock in the birth weight in the first and second month after calving as it was 13.20,19.41 kg , while there are no significant differences in the total weight gain (from birth to weaning) among the three flocks. Higher (P<0.05) percentage of birth mortality was recorded in the unimproved flock (20%) while it was the lowest percentage in the grazing flock (9.5%).The improved flock showed highest rate of ewes mortality (7.5%) and unimproved flock (5%), no ewes mortality were observed in the grazing flock during the experimental period. The grazing and unimproved flocks showed higher milk production (1127.5, 927.08 cm3) during the fourth month after calving, while the lower milk production was in the unimproved flock during the first and second month after birth.